Potency of turmeric (Curcuma longa L.) extract and curcumin as anti-obesity by inhibiting the cholesterol and triglycerides synthesis in HepG2 cells - Budiman, Iwan; Tjokropranoto, Rita; Widowati, Wahyu; Fauziah, Nurul; Erawijantari, Pande Putu (International Journal of Research in Medical Sciences, 2017)
Background: Adipocytes accumulate triacylglycerol when excessive food consumption. Adipocyte dysfunction plays an important role in the obesity development. People with a body weight 40 % heavier than the average body weight population at risk of death two times greater than the average body weight. The use of anti-obesity drugs have many side effects, so it is necessary to find the anti-obesity drug with low toxicity. This ex vivo study was conducted to determine the activity of C. longa L. extract in inhibiting triglycerides and cholesterol synthesis and lipid droplet formation on HepG2 cells compared to curcumin. Methods: Anti-obesity activity includes reduced formation of lipid droplet in HepG2 cells can be observed using oil red O staining method. The measurement of triglyceride level was performed according to Randox protocol using Randox TR 210 assay kit. Lipolytic activity by measuring cholesterol levels was performed based on Randox CH 200 kits. Results: This study suggested that the extract of C. longa L. and curcumin have potential anti-obesity compounds. C. longa L. extract have higher activity in inhibiting triglycerides and cholesterol synthesis compared to curcumin with inhibition activities 70.43% and 66.38% respectively in the highest concentration. Conclusion: The C. longa extract posses the anti-adipogenesis potential on inhibiting the synthesis of triglycerides and cholesterol and lipid droplet formation in HepG2 cell as anti-obesity parameters better than curcumin.